Efficacy of Guided iCBT for Depression and Mediation of Change by Cognitive Skill Acquisition. Issue 2 (March 2018) - Forand, Nicholas R.; Barnett, Jeffrey G.; Strunk, Daniel R.; Hindiyeh, Mohammed U.; Feinberg, Jason E.; Keefe, John R.
Abstract: Guided internet CBT (iCBT) is a promising treatment for depression; however, it is less well known through what mechanisms iCBT works. Two possible mediators of change are the acquisition of cognitive skills and increases in behavioral activation. We report results of an 8-week waitlist controlled trial of guided iCBT, and test whether early change in cognitive skills or behavioral activation mediated subsequent change in depression. The sample was 89 individuals randomized to guided iCBT ( n = 59) or waitlist ( n = 30). Participants were 75% female, 72% Caucasian, and 33 years old on average. The PHQ9 was the primary outcome measure. Mediators were the Competencies of Cognitive Therapy Scale–Self Report and the Behavioral Activation Scale for Depression–Short Form. Treatment was Beating the Blues plus manualized coaching. Outcomes were analyzed using linear mixed models, and mediation with a bootstrap resampling approach. The iCBT group was superior to waitlist, with large effect sizes at posttreatment (Hedges' g = 1.45). Dropout of iCBT was 29% versus 10% for waitlist. In the mediation analyses, the acquisition of cognitive skills mediated subsequent depression change (indirect effect = -.61, 95% bootstrapped biased corrected CI: -1.47, -0.09), but increases in behavioral activation did not. iCBT is an effective treatment for depression, but dropout rates remain high. Change in iCBT appears to be mediated by improvements in the use of cognitive skills, such as critically evaluating and restructuring negative thoughts. Highlights: Guided iCBT for depression was superior to waitlist, with large effect sizes Dropout in iCBT was 29% despite a coaching protocol designed to improve adherence Depression change in iCBT was mediated by improvement in cognitive skills We failed to find evidence that depression change in iCBT was mediated by improvement in behavioral activation